2016
DOI: 10.1016/j.susc.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the incorporation of nitrogen in titanium and its influence on the electrochemical corrosion resistance in acidic media

Abstract: The role of the nitrogen incorporation into titanium, its chemical nature, the location in the titanium lattice and its electrochemical performance were investigated by a combination of several spectroscopy and microscopy techniques using samples prepared by CVD of NH 3 at different temperatures and successive electrochemically tested in 1 M of HClO 4 . We found that nitrogen is incorporated in either the interstitial or substitutional site of the lattice depending on the preparation temperature modifying stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The binding energy values represent the valence state and the density of charge near the atoms. In Figure 4 a, the Ti 2p peaks for sample X show the typical binding energy values of Ti +4 , but the broadened shape on the low energy side reveals the presence of some low value ions of Ti, such as Ti 3+ and Ti 2+ , similar to previous reports on anodized titanium [ 14 ]. After thermal oxidation, the Ti 2p peaks remained in similar shapes, while the major change was observed in O 1s spectra, as presented in Figure 4 b.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The binding energy values represent the valence state and the density of charge near the atoms. In Figure 4 a, the Ti 2p peaks for sample X show the typical binding energy values of Ti +4 , but the broadened shape on the low energy side reveals the presence of some low value ions of Ti, such as Ti 3+ and Ti 2+ , similar to previous reports on anodized titanium [ 14 ]. After thermal oxidation, the Ti 2p peaks remained in similar shapes, while the major change was observed in O 1s spectra, as presented in Figure 4 b.…”
Section: Resultssupporting
confidence: 85%
“…Sul et al reported that a reduction in the current density appeared by altering the temperature and concentration of electrolyte [ 12 ]. Some of the advantages observed by applying anodizing processes include reduced cost (no necessity of gas shielding or costly vacuum conditions); simple and easy operation variables to fabricate the required coatings; ecological favorability, since there is no harmful emission involved in the operation; good adhesion; and easy incorporation with different surface treatments, such as thermal oxidation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from fitting the Ti 2p high-resolution spectra, T1 and T3 peaks were assigned to 2p 1/2 and 2p 3/2 energy levels of Ti 4+ , respectively. Next, T2 and T4 were appointed to 2p 1/2 and 2p 3/2 energy levels of Ti 3+ , respectively. The latter suggests the formation of oxygen vacancies or TiN x species . However, this can be partially or exclusively the effect of the Ar ion etching process .…”
Section: Results and Discussionmentioning
confidence: 99%
“… 50 52 The latter suggests the formation of oxygen vacancies 53 or TiN x species. 54 However, this can be partially or exclusively the effect of the Ar ion etching process. 55 In turn, the T5 and T6 pair is originating most probably from titanium oxynitride.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, homogeneous deposition on complex three dimensional architectures or porous conductive substrates is challenging. As an alternative, TiN surface can be obtained through the thermal treatment of Ti in a nitrogen rich atmosphere [42][43][44][45]. This nitriding process allows the treatment of a large number of samples in a single batch, including complex geometries and porous materials, owing to the excellent infiltration capabilities of gas.…”
Section: Introductionmentioning
confidence: 99%